Entrepreneurship and Poverty Reduction In Cameroon: A Vector Autoregressive Approach - Wujung, Vukenkeng Andrew; Mbella, Mukete Emmanuel (Archives of Business Research, 2014)
This paper investigates the effect of entrepreneurship on poverty alleviation in Cameroon and determines the nature of the causality that exists between them using the vector autoregressive approach. The study uses data from the Cameroon National Institute of statistics and World Bank Development Indicators for the period 1980-2013. The results show that entrepreneurship has a significant negative impact on poverty in Cameroon and that there exists a significant bi-directional positive causality between entrepreneurship and poverty reduction. From a policy perspective, the study concludes that training and retraining of entrepreneurs as well as organizing entrepreneurship skills acquisition programmes are vital to boost entrepreneurship in order to reduce poverty in the country. JEL Classification: E23, F2, F21, F43 Keywords: Entrepreneurship, Poverty reduction, Vector Autoregressive Approach